IDENTIFIKASI DAN MINIMASI WASTE PADA PROSES PRODUKSI KERIPIK PISANG KEJU DENGAN VALUE STREAM MAPPING DAN KAIZEN - Rasyid, Abdul; Junus, Stella; Ramadhani, Indah; Uloli, Hendra; Hasanuddin, Hasanuddin (Universitas Bina Taruna Gorontalo, 2023)
This study aims to determine the types of waste in the cheese banana chips production process at Flamboyan UKM and find out how to minimize waste in the production process. This study uses the lean manufacturing method in evaluating the formulation to identify and reduce waste that occurs in Flamboyan UKM. The results of this study are two wastes, namely waiting time where waiting activities occur in the stacking of finished products in the draining process with a time of 247.13 seconds and in the cooling process with a time of 251.77, and waste defects where there are cracked chips, charred chips and packaging processes that are not good , causing the chips to not be crispy. The conclusion of this research is to minimize waste wasting time by adding a spinner machine in the draining process, as well as for the cooling process to minimize waste waiting time for the chips to be separated into several containers. Furthermore, for waste defects, conduct training for employees and carry out product checks or checks. Suggestions for Flamboyan SMEs need training for employees to be more effective in carrying out good work and making continuous improvements in order to get good product results